Hunger for farmland among female farmers in Limpopo Province: bodies, violence and land. Issue 4 (2nd October 2018) - Makhetha, Esther; Hart, Tim
Abstract: This article explores intersections between women's bodies, violence and land amongst female farmers in Limpopo Province, South Africa. We explore how female farmers negotiate access to land through their own agency and resistance on a daily basis by analysing their narratives and experiences in their quest to access and use land for farming. Based largely on ethnographic interviews and observations the article argues that women's involvement in farming should be considered not only as an economic survival strategy, but also as an indication of how the female farmers express resistance and agency in their pursuit to acquire land for farming. This article contributes to the body of literature that explores the relationship between women's bodies, violence and access to land but does so by focusing on land redistribution and some of the challenges it poses to women of different backgrounds and degrees of social power and influence. The paper make four recommendations about how the government can improve its focus on female farmers and get to grips with gender mainstreaming and needs.